2014
DOI: 10.3109/10408444.2014.910751
|View full text |Cite
|
Sign up to set email alerts
|

Human relevance framework for rodent liver tumors induced by the insecticide sulfoxaflor

Abstract: Sulfoxafl or, a novel active substance that targets sap-feeding insects, induced rodent hepatotoxicity when administered at high dietary doses. Specifi cally, hepatocellular adenomas and carcinomas increased after 18 months in male and female CD-1 mice at 750 and 1250 ppm, respectively, and hepatocellular adenomas increased after 2 years in male F344 rats at 500 ppm. Studies to determine the mode of action (MoA) for these liver tumors were performed in an integrated and prospective manner as part of the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Furthermore, the doses of the chemicals administered are of a single concentration and duration albeit the MTD and so essentially the preserved gene networks that we discovered are not dynamic in nature. It is important to emphasize that the gene modules described here are a starting point for MOA characterization and greater nuance will likely be required to characterize mechanistic processes associated with specific receptors (e.g., PPAR-α vs. AhR; LeBaron et al, 2014 ; Becker et al, 2015 ) or chemicals with mixed MOAs. An illustration of such nuance was shown in a recent study in which clear subgroups of chemicals in the RM class of compounds was observed (De Abrew et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the doses of the chemicals administered are of a single concentration and duration albeit the MTD and so essentially the preserved gene networks that we discovered are not dynamic in nature. It is important to emphasize that the gene modules described here are a starting point for MOA characterization and greater nuance will likely be required to characterize mechanistic processes associated with specific receptors (e.g., PPAR-α vs. AhR; LeBaron et al, 2014 ; Becker et al, 2015 ) or chemicals with mixed MOAs. An illustration of such nuance was shown in a recent study in which clear subgroups of chemicals in the RM class of compounds was observed (De Abrew et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The postulated MOA is similar to that of certain other nongenotoxic agents which are CAR activators. 17,19,[29][30][31][32][33] Furthermore, multiple alternative MOAs have been excluded. Overall, these data strongly support that the postulated MOA for metofluthrin-and momfluorothrin-produced rat hepatocellular tumours is mediated by CAR activation.…”
Section: Moa Analysis For Metofluthrin-and Momfluorothrin-induced Ratmentioning
confidence: 99%
“…As mentioned above, numerous publications have mentioned that the CARmediated MOA is qualitatively not relevant to humans, based on the lack of the key event of an increased cell proliferation in hepatocellular tumorigenesis induced by the prototypic CAR activator PB. 15,17,19,20,[29][30][31][32][33][36][37][38][39] A cultured human hepatocyte study…”
Section: Key Events Associative Eventsmentioning
confidence: 99%
“…Normally phosphorylated and complexed with heat shock protein 90 (HSP90) and cytosolic CAR retention protein (CCRP) in cytosol, CAR can become activated, e.g., in mice by binding to a ligand, such as 1,4-bis [2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP), or in mice or humans by being dephosphorylated via phenobarbital-mediated recruitment of protein phosphatase 2 (PP2A), after which CAR translocates to the nucleus where it heterodimerizes with nuclear receptor RXR and then interacts with promoter complexes of target genes that regulate many physiological processes including lipid metabolism, glucose metabolism, hormonal regulation, cell growth, wound healing, and apoptosis [1][2][3][4][5][6][7]. CAR is thought to promote liver tumors in some rodents by stimulating downstream (e.g., CYP2b, Wisp, FoxM1, cMyc) receptors, multidrug transporters and resistance genes, and related epigenetic modifications (e.g., regions of altered DNA methylation) and microRNA dysregulation (e.g., miR-182 and miR-802 upregulation and miR-122 downregulation) that facilitate hepatocellular proliferation and associated shifts in energy and growth-directed metabolism [2,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], particularly when coupled with -catenin activation [23].…”
Section: Introductionmentioning
confidence: 99%